The Impact of Broadband on Economic Activity in Rural Areas: Evidence from German Municipalities - Nadine Fabritz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
This paper investigates the impact of broadband availability on economic activity as measured by local employment rates. Using panel data on broadband coverage in 8,460 West German municipalities for the period from 2005 to 2009, we find, in fixed effectsregressions, an overall positive, but economically rather limited, relationship between local employment and local broadband infrastructure. The effect is larger in rural municipalitiesand is likely to stem from the service sector.
Keywords: L96; O10; O20; R23; 330; Broadband; local economic development; local employment